Pengaruh Tingkat Pengangguran, Indeks Pembangunan Manusia dan Investasi Terhadap Kemiskinan di Kalimantan Selatan - Vyra Luthfia Annisa; Nasruddin Nasruddin (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2022)
This study aims to determine which variables affect poverty in South Kalimantan. This study also uses multiple linear regression analysis tools in the Effect of Unemployment Rate, Human Development Index, and Investment on Poverty in South Kalimantan. They have been using secondary data for ten years (2010-2019). The results of analysis regression, the dependent variable, namely the Unemployment Rate variable and the Human Development Index, has a significant effect on poverty in South Kalimantan. While the dependent variable, namely the investment variable, has no significant impact on poverty in South Kalimantan. From the regression analysis results, the dominant variable is the Human Development Index for Poverty in South Kalimantan. because the higher the level of quality of human development in an area, it can reduce poverty in that area